Electron‐Scale Measurements of Antidipolarization Front - Yin Xu; Huishan Fu; Jinbin Cao; Chengming Liu; Cecilia Norgren; Zuzheng Chen (Geophysical Research Letters)
Abstract Antidipolarization fronts (ADFs), usually formed at the leading edge of the tailward reconnection jets in the Earth's magnetotail, are characterized by sharp enhancements of southward magnetic field (negative Bz). The fine structures at electron scale of the ADFs have not been studied so far, due to instrumental limitations and large separation of previous spacecraft. Here, we use the Magnetospheric Multiscale mission to investigate the structure and dynamics of an ADF at electron scale. We find an intense current at the ADF, with the parallel current carried by a fast electron jet and the perpendicular current contributed by ion flow. Strong electric fields are found at the front and balanced by Hall term. The ion current leads to strong energy conversion, transforming the electromagnetic energy into particle energy. Our study makes essential steps toward understanding ADF dynamics in the magnetotail.